2015
DOI: 10.1136/heartjnl-2015-308066.147
|View full text |Cite
|
Sign up to set email alerts
|

147 Burden of Undiagnosed Hypertension in Sub-Saharan Africa: A Systematic Review and Meta-Analysis

Abstract: The burden of hypertension in Sub-Saharan Africa has been increasing over the past few decades. However, a large proportion of the population with hypertension remains undiagnosed, untreated, or inadequately treated, contributing to the rising burden of cardiovascular disease in the region. We conducted a systematic review and meta-analysis to assess the recent burden of hypertension in Sub-Saharan Africa, based on studies published between 2000 and 2013. We pooled data from 33 surveys involving over 110 414 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

17
147
4
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(171 citation statements)
references
References 0 publications
17
147
4
3
Order By: Relevance
“…Emerging epidemiological data from Nigeria [1] and indeed the entire sub-Saharan Africa [2][3][4] indicate that hypertension has become a major public health challenge. Accurate measurement and diagnosis of hypertension is key to overcoming this challenge.…”
Section: Introductionmentioning
confidence: 98%
“…Emerging epidemiological data from Nigeria [1] and indeed the entire sub-Saharan Africa [2][3][4] indicate that hypertension has become a major public health challenge. Accurate measurement and diagnosis of hypertension is key to overcoming this challenge.…”
Section: Introductionmentioning
confidence: 98%
“…2 Systematic reviews from South Asia, Arab and sub-Saharan countries showed prevalence of hypertension in these regions of 27, 29.5 and 30%, respectively. [3][4][5] Hypertension can be managed through lifestyle modifications and adherence to anti-hypertensive medication. 6 The World Health Organization (WHO) has defined adherence as 'The extent to which a person's behavior-taking medication, following a diet, and/or executing lifestyle changes-corresponds with agreed recommendations from a health care provider'.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, a substantial proportion of hypertensive treated individuals fail to achieve long-term BP control 5–7. For instance, in sub-Saharan Africa, only as few as 7% of treated patients with hypertension have controlled BP 8. Several factors account for poor BP control, including absence of hypertension treatment guidelines or non-adherence to these guidelines by physicians, non-compliance to pharmacological treatment or life styles changes 6.…”
Section: Introductionmentioning
confidence: 99%